2021
DOI: 10.1007/s11082-021-02980-2
|View full text |Cite
|
Sign up to set email alerts
|

Large core optical elastomer splitter fabricated by using 3D printing pattern

Abstract: The design, fabrication and properties of the large core 1x2Y optical planar splitter using optical elastomers for cladding and core is demonstrated. The splitters were designed by beam propagation method optimized for operation wavelength 650 nm. The splitters were fabricated using epoxy polymer pattern fabricated by Stereolithography 3D printing technology. The dimensions of the splitters were optimized for assembling optical fiber with core diameter 500 µm. The splitter shows optical losses around 1.48 dB a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Prajzler et al reported PMDS waveguides to have a low refractive index ( n = 1.41, λ = 589 nm) [ 66 ] and low optical absorption loss (1.8 dB/cm, λ = 532 nm; 1.0 dB/cm, λ = 633 nm) [ 110 ]. The same group also reported POF splitters with silicon optical elastomer LS-6943 as core and PDMS as cladding, which have a core refractive index around 1.433 and cladding refractive index around 1.416 at 532 nm wavelength [ 111 ]. Shentu et al reported a no-core PDMS fiber with strain sensitivity of 3.5070/ε (large-scale strain from 0% to 40%) [ 112 ].…”
Section: The Materials Of Polymer Optical Fibermentioning
confidence: 99%
“…Prajzler et al reported PMDS waveguides to have a low refractive index ( n = 1.41, λ = 589 nm) [ 66 ] and low optical absorption loss (1.8 dB/cm, λ = 532 nm; 1.0 dB/cm, λ = 633 nm) [ 110 ]. The same group also reported POF splitters with silicon optical elastomer LS-6943 as core and PDMS as cladding, which have a core refractive index around 1.433 and cladding refractive index around 1.416 at 532 nm wavelength [ 111 ]. Shentu et al reported a no-core PDMS fiber with strain sensitivity of 3.5070/ε (large-scale strain from 0% to 40%) [ 112 ].…”
Section: The Materials Of Polymer Optical Fibermentioning
confidence: 99%
“…As another possibility of the AM method in transparent materials, the development of waveguides was explored not only using plastics [ 25 ], but also in glass structures [ 26 ]. In this scenario, the development of optical devices using polymers [ 27 ] and, especially, POFs [ 28 ] result in an additional possibility in optical fiber technology. These POFs are generally used in the development of sensors, where the integration of AM methods results in multiparameter sensing [ 29 ] as well as the performance enhancement in temperature [ 30 ] and force [ 31 ] sensors.…”
Section: Introductionmentioning
confidence: 99%